FEEDING MANAGEMENT OF BROILER PARENT STOCK PHASE LAYER IN PT. CHAROEN POKPHAND JAYA FARM UNIT 8 PROBOLINGGO JAWA TIMUR - A. J., Marwansyah; Miwada, I N.S; Puger, A. W. (Jurnal Peternakan Tropika, 2019)
The activity aims to find out and assess the feeding management of broiler parent stock phase layer at PT. Charoen Pokphand Jaya Farm Unit 8 Probolinggo East Java in the implementation of student work practices/PKM at the Faculty of Animal Husbandry, Udayana University. Activities carried out through interviews, observation and direct work practices. The results of the activity showed that the feeding management of broiler parent stock phase layer at PT. Charoen Pokphand Jaya Probolinggo East Java Farm Unit 8 has been well implemented. The quality of feed is considered well and meets the needs of livestock. The feed given is feed into pellets "Charoen 535 CT" for males and "Charoen 534-2T" for females. The frequency of feeding is done once a day. Male feed is given as much as ± 161.3 g/head/day while for females given as much as ± 142.3 g/head/day. The prediction of consumption of nutrient broiler parent stock phase layer feed includes protein, fat, fiber, ash, calcium, and phosphorus for males, namely 22.6; 4.8; 9.7; 11.3; 1.5; and 0.97 g/head/day while for females that is 21.8; 4.3; 8.5; 17,1; 4.6; and 0.85 g/head/day. At PKM at PT. Charoen Pokphand Jaya Farm Unit 8, Probolinggo, East Java, students are actively involved in the whole series of maintenance and management activities of broiler parent stock. Based on the results of the study it can be concluded that the feeding management of broiler parent stock phase layer at PT. Charoen Pokphand Jaya Probolinggo East Java Farm Unit 8 has been implemented well, this is seen from high egg production, daily increase in body weight of chickens, and low mortality in chickens.   Keywords: broiler parent stock, feeding management, feeding quality